Minimally Invasive Mitral Valve Surgery After Transcatheter Edge-to-Edge Repair. Issue 1 (January 2022) - Pizano, Alejandro; Riojas, Ramon; Ailawadi, Gorav; Smith, Robert L.; George, Timothy; Gerdisch, Marc W.; Di Eusanio, Marco; Castillo-Sang, Mario; Ramlawi, Basel; Rodriguez, Evelio; Morse, Michael A.; Doolabh, Neelan S.; et al.
Ob jective: Up to 28% of patients may need mitral valve (MV) surgery after transcatheter edge-to-edge repair (TEER). This study evaluates the outcomes of minimally invasive MV surgery after TEER.Methods: International multicenter registry of minimally invasive MV surgery after TEER between 2013 and 2020. Subgroups were stratified by the number of devices implanted (≤1 vs >1), as well as time interval from TEER to surgery (≤1 year vs >1 year).Results: A total of 56 patients across 13 centers were included with a mean age of 73 ± 11 years, and 50% were female. The median Society of Thoracic Surgeons Predicted Risk of Mortality (STS PROM) score for MV replacement was 8% (Q1-Q3 = 5% to 11%) and the ratio of observed to expected mortality was 0.9. The etiology of mitral regurgitation (MR) prior to TEER was primary MR in 75% of patients and secondary MR in 25%. There were 30 patients (54%) who had >1 device implanted. The median time between TEER and surgery was 252 days (33 to 636 days). Hemodynamics, including MR severity, MV area, and mean gradient, significantly improved after minimally invasive surgery and sustained to 1-year follow-up. In-hospital and 30-day mortality was 7.1%, and 1-year actuarial survival was 85.6% ± 6%.Conclusions: Minimally invasive MV surgery after TEER may be achieved as predicted by the STS PROM. Most patients underwent MV replacement instead of repair. As TEER is applied more widely, patients should be informed about the potential need for surgical intervention over time after TEER. These discussions will allow better informed consent and post-procedure planning.